Can universities play an active role in fostering entrepreneurship in emerging ecosystems? A case study of the University of São Paulo. (2018) - Ribeiro, Artur Tavares Vilas Boas; Zancul, Eduardo De Senzi; Axel-Berg, Justin Hugo; Plonski, Guilherme Ary
The present study aims to identify patterns and roles that can be played by research universities in emerging entrepreneurship ecosystems. Its methodology is based on a case study of the University of São Paulo, analysing three startups born inside the university and the characteristics of its development processes. As a conclusion, we identify strategies to deal with bottlenecks and enhancers of an emerging entrepreneurship ecosystem, as well as patterns on how a university can stimulate entrepreneurship in a context of regional constraints – such as: 1) building interfaces between academic environments; 2) applying processes such as customer development using university capabilities; 3) empowering grassroots movements for entrepreneurship.